Para além da auto-gestão: quando os líderes geram auto-líderes - Quinteiro, Pedro Marques; Curral, Luís Alberto; Passos, Ana Margarida (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The ending of the 20th century has seen the growth of Self-management theory, latter on followed by the advent of Self-leadership Theory (Manz, 1986). Modestly developed over the past twenty years, Self-leadership has now begun to receive a more deserved attention as it is understood as an adaptive competence that influences individual and collective though and action (Neck & Manz, 2010). Being well known as a predictor of individual and team effectiveness, creativity, innovation, motivation and organizational change adaptation (Neck & Houghton, 2006; Curral & Marques-Quinteiro), the relationship between self-leadership and leadership dynamics is yet to be clearly understood. This paper aims to give a theoretical contribution to both Self-leadership and Leadership literatures, through the proposal of a theoretical explanation of the relation between both constructs, one that goes beyond what has been said till now on this topic.